Mycobacterium bovis deleted in mce2 and phoP loci protects C57BL/6 mice against tuberculosis - Garcia, Elizabeth Andrea; Bianco, María Veronica; Blanco, Federico Carlos; Bigi, Fabiana (2017)
Here we confirm the efficacy of MbΔmce2-phoP to protect mice against bTB challenge and we demonstrated that this new attenuated strain is safer than our previous bTB vaccine MbΔmce2. Altogether these results support the further assessment of this candidate in cattle model of bTB.Experiments with mice were performed in compliance with the regulations of the Institutional Animal Care and Use Committee (CICUAE) of INTA (61/2014)..